Legal Study on the Development of Leading Tourist Areas to Increase Community Participation - Triwanda Sekar Dewi; Endang Sutrisno (International Journal Labs, 2026)
Tourism development has become an important strategy for regional economic growth and community welfare improvement. However, tourism development often faces challenges related to limited community involvement, weak institutional coordination, and the effectiveness of legal frameworks in ensuring inclusive participation. This study aims to examine the legal aspects of developing leading tourism areas to increase community participation, particularly through the implementation of tourism regulations in Kuningan Regency. This research employed a normative juridical method with a statutory and conceptual approach. Data were obtained through the analysis of primary legal materials, including tourism laws, regional regulations, and village regulations, supported by secondary legal materials from relevant academic literature. The data were analyzed using the theory of legal effectiveness, focusing on legal factors, law enforcement factors, facilities and infrastructure, and community cultural factors. The results show that the development of leading tourism areas in Kuningan Regency has a strong legal foundation through national, regional, and village-level regulations. The implementation of these regulations has encouraged community participation through community-based tourism management, particularly through the role of Village-Owned Enterprises (BUMDes) in Cibuntu Tourism Village and Kaduela Tourism Village. However, several challenges remain, especially regarding infrastructure improvement and institutional strengthening. This study concludes that effective legal arrangements supported by institutional capacity and community awareness are essential for creating sustainable tourism development. The findings contribute to tourism governance literature by emphasizing the importance of regulatory effectiveness in strengthening community participation